Adaptational biology - Prosser, C. Ladd (Wiley, 1986)
"A Wiley-Interscience publication."; Includes bibliographical references and index.; Includes index.; Presents modern biology from a broad perspective. Deals with theory of adaptation, origin of life, dynamic genetics, adaptations to the physical environment, animal behavior with extrapolation to human nature, properties of simple nervous systems, and more. Controversial topics, such as gradualism vs. saltation, are addressed from the viewpoint of a physiologist.